PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE TGT (TEAM GAMES TOURNAMENT) MENGGUNAKAN MEDIA GAMBAR UNTUK MENINGKATKAN MINAT BELAJAR SISWA PADA PEMBELAJARAN PENDIDIKAN PANCASILA DI KELAS XI SMAN 16 PADANG - Gusfia Yollanda; Harisnawati; Asril (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The low learning interest of eleventh-grade students in Pancasila Education at SMA Negeri 16 Padang was reflected in their limited attention, participation, and active engagement during the learning process. This condition was influenced by the predominance of lecture-based instruction and the limited use of varied learning media. This study aimed to describe the implementation of the Teams Games Tournament (TGT) cooperative learning model assisted by picture media in improving students' learning interest in Pancasila Education in Class XI F.3 of SMA Negeri 16 Padang. This study employed a descriptive qualitative approach conducted during the second semester of the 2025/2026 academic year. The research participants consisted of a Pancasila Education teacher, the vice principal for curriculum, and five students. Data were collected through observation, structured interviews, and documentation, and were analyzed using the interactive model of Miles and Huberman, including data collection, data reduction, data display, and conclusion drawing. Data validity was ensured through source triangulation. The findings revealed that the implementation of the TGT model supported by picture media was carried out through material presentation, group formation, discussion, tournaments, score awarding, and team recognition. The implementation of the model enhanced students' attention, enjoyment, active participation, initiative, and learning effort during Pancasila Education lessons. Therefore, the Teams Games Tournament (TGT) cooperative learning model assisted by picture media was effective in improving students' learning interest. The findings imply that the TGT model supported by picture media can serve as an innovative, interactive, and student-centered learning alternative, while also providing a useful reference for teachers in improving the quality of Pancasila Education instruction